2022
DOI: 10.1002/lary.30098
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Assessment of Blood Transfusions in Elective Thyroidectomy Based on 180,483 Patients

Abstract: Objectives To assess the incidence, risk factors, and complications of blood transfusions (BTs) in elective thyroidectomy patients. Methods A retrospective cohort study was conducted using the American College of Surgeons National Surgical Quality Improvement Program. Adult patients who underwent elective thyroidectomy from 2005 to 2019 were divided into two cohorts based on whether they received BT or not. Multivariable binary logistic regression models were used to identify risk factors of BT and its impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…The present study indicated that most complications of blood transfusion occurred in people over the age of 50, which is similar to the study by Waqar et al (24), females which is similar to studies by Gotekar and Khade (25) and Amiri et al (26), and the O blood group which is similar to study Asgharniya et al (27). In their study, Asgharnia et al (27) and Gotekar and Khade (25) reported the most complications of blood transfusion in people under 50, which is different from the present study.…”
Section: Discussionsupporting
confidence: 92%
“…The present study indicated that most complications of blood transfusion occurred in people over the age of 50, which is similar to the study by Waqar et al (24), females which is similar to studies by Gotekar and Khade (25) and Amiri et al (26), and the O blood group which is similar to study Asgharniya et al (27). In their study, Asgharnia et al (27) and Gotekar and Khade (25) reported the most complications of blood transfusion in people under 50, which is different from the present study.…”
Section: Discussionsupporting
confidence: 92%